A pesca no reservatório da usina hidrelétrica de Tucuruí, Estado do Pará, Brasil - Cintra, Israel Hidenburgo Aniceto (2009)
Fisheries in the reservoir by the Tucuruí dam (Northern Brazil) constitute an important source of occupation, food production and income for the local population. To learn more about the fisheries and provide subsidies for sustainable measures, we looked into the current situation of the fishermen, fisheries, landing and support infrastructure, production chain and biological aspects of the main species captured—the mapará catfish (Hypophthalmus marginatus) and the South American silver croaker (Plagioscion squamosissimus). Data were collected through direct observation, interviews, semi-structured questionnaires, systematic tracking of landings and experimental fishing. Most of the local fishermen were male (68%), married (74%) and were originally from Pará (55%) or Northeastern Brazil (42%). On the average, the fishermen were aged 37 years, had 3.85 children, displayed low level of schooling, and 41% had never had another occupation. The most important form of professional organization was the trade union. Fishing boats included dugouts, canoes, aluminium outboard motor boats, inboard motor boats and catch storage vessels. Fishing was mostly done with gill nets and line and hook. Apart from the catfish and the silver croaker, the peacock bass (Cichla monoculus and Cichla sp.) and the curimatã (Prochilodus nigricans) were also frequently captured. The region had practically no landing and support infrastructure and ice supplies were scarce. The mapará catfish has isometric allometry. Starting at 41 cm total length, mature females were observed throughout the year but peaked in the fourth and first quarter. The silver croaker has positive allometry. Mature females measured ?32.4 cm. Spawning was observed around the year, with peaks in September and October. The local production chain did not extend beyond the sale of the fish to middlemen. The study highlights the importance of artisanal fisheries in the Tucuruí reservoir and points to the need for measures ensuring the sustainability of the activity.